Sustainable Development Goals Related to Agriculture and the EU’s Main Development Strategies - Krzyżanowski, Julian T. (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2024)
The paper deals with the United Nations Sustainable Development Goals (SDGs) of 2015 and their relation to agricultural and rural activities. Over the years, many strategic documents have been created, especially within the European Union. The aim of this paper is to analyse the most important ones, to highlight the outlined objectives related to agriculture and rural areas and to compare them with the SDGs. A review of major EU CAP documents published in recent years, as well as the EU economic, agricultural and environmental strategies, has been undertaken. The analysis is set against the background of the UN declarations and agendas. Research shows that of the 17 Sustainable Development Goals (SDGs) promoted by the United Nations, 16 are directly or indirectly linked to agriculture and are implemented through the activities of the Common Agricultural Policy (CAP). It could also be said that the SDGs served as a kind of starting point for many important documents, shaping, among other things, the future of the CAP.